Comparison of bone density changes in rabbit mandible using different osteoplastic materials - Chelpanova , I.V. (Морфологія / Morphologia / Morfologìâ, 2024)
Background. Nowadays, premature tooth loss is a significant problem not only in dentistry but also in general medicine. The effectiveness of dental prosthetics is largely determined by the condition of the jaw bone. Therefore, osteoplastic materials find wide application in filling bone defects that occur after injuries and tooth extractions, with the goal of preserving the volume and quality of bone tissue in the angular regions of the jaws. Advanced imaging techniques allow for the assessment of bone quality using mineral density as a biomarker. Experimental methods play a crucial role in understanding the processes occurring in the body during the development of pathological conditions. Objective. The aim of our study was to investigate the characteristics of mineral density of rabbit mandible bone and its restoration after implantation of different osteo plastic materials into its cavity. Methods. Adult male rabbits aged 6-7 months and weighing 2.5-3 kg were used for the study. The animals were divided into a control and two experimental groups. The control group included animals with bone tissue defects that healed under a blood clot. Intact animals were examined to determine the normal bone density in the area of injury. Experimental group 1: Animals with bone defects filled with Collacone (Botissdental), a natural matrix for new bone cell formation. Experimental group 2: Animals with bone defects filled with Collacone (Botissdental), followed by intramuscular injections of lincomycin hydrochloride (30% solution) at a dosage of 25 mg/kg once daily, starting 6 days after the injury. Results and conclusion. When healing a bone injury under a blood clot, the dynamics of bone density in the area of injury have a smooth course with a slight increase in values compared to normal. When filling the defect with osteoplastic materials, we observe pronounced dynamics of changes in the studied indicator with sharp fluctuations at different stages of the experiment (depending on the material used). Comparing the dynamics of bone density in the angular region of the mandible after filling the defect with Collacone (Botissdental) with the control allowed us to establish its characteristics, specific for the experimental and control groups of animals. A significant difference was found when comparing normal bone density values with those established at different time points of post-traumatic bone regeneration with the Collacone-filled defect: 1 day, 7 days, 14 days, 21 days, 28 days, 35 days, 56 days (p<0.001), and 84 days (p<0.05). Comparing the studied indicators established for this experimental group over different periods of the experiment revealed a significant difference between the values recorded after 1 day and 56 days (p<0.05), 1 day and 84 days (p<0.05), 14 days and 28 days (p<0.05), 14 days and 56 and 84 days (p<0.01), 21 days and 84 days (p<0.05), 35 days and 84 days (p<0.05). When comparing bone density indicators in the area of injury in animals whose bone defect was filled with Collacone (Botissdental) and intramuscularly injected with lincomycin hydrochloride, a significant difference (p<0.01) was found in their values established over different periods of the experiment. Specifically, a significant difference was found with normal values for those established over 1-56 days (p<0.001), and 84 days (p<0.05) of the experiment. A significant difference (p<0.05) was also found between the studied indicators established at different time points of post-traumatic bone regeneration in animals included in this experimental group. In particular, a significant difference (p<0.05) was found between the indicators of 1 day and 35 days, 56 days, 84 days; 7 days, 14 days and 28-84 days; 21 days, 28 days, and 35-84 days. When filling the bone defect with Collacone (Botissdental) and healing under a blood clot, bone density in the area of injury remains significantly higher than normal values.